Pendidikan ideal perspektif Tagore dan Ki Hajar Dewantara dalam pembentukan karakter peserta didik - Marzuki, Marzuki; Khanifah, Siti (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
The research aims to study the thought of Rabindranath Tagore and Ki Hajar Dewantara with the ideal education related in formation of students character. This research is a literature review using content analysis approach. Sources of data in the form of primary data and secondary data on thought of two leaders in education. Data were analyzed qualitatively with the inductive approach. The results showed that 1) Rabindranath Tagore saw education based on freedom and love. Learning approach undertaken by Rabindranath Tagore in the education system is experiential learning; 2) Ki Hajar Dewantara developed a Among system in education which is an effort to advance the development of morality (inner strength), mind (intellect), and physical students; and 3) there is a link between thought of Rabindranath Tagore and thought of Ki Hajar Dewantara on looking at the education and development of ideal education system.